IPM and Organic courses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The International Agricultural Centre is offering a course on Development of IPM Approaches (12 May - 9 June 2002) and parallel courses on the Role of Pesticides in IPM, and Organic Farming: Principles and Applications, from 10 to22 June 2002.IACPO...